Interactional and procedural practices in managing coopetitive tensions - Annika Tidström; Paavo Ritala; Kirsi Lainema (Emerald, 2022)
Purpose
The purpose of this paper is to explore interactional and procedural practices in managing tensions of coopetition (simultaneous collaboration and competition between firms).
Design/methodology/approach
Through an in-depth literature review of prior research within coopetition and strategy-as-practice fields, and by using two illustrative empirical examples, the authors develop a framework for preventing and managing coopetitive tensions through combinations of procedural and interactional practices.
Findings
The authors identify tensions related to strategizing, task and resource allocation, as well as knowledge sharing. Furthermore, they demonstrate potential ways of how these tensions can be prevented, resolved and managed.
Research limitations/implications
The findings show that the analysis of tensions in coopetition would benefit from a holistic, multilevel approach that recognizes practices that are interactional (i.e. face-to-face interactions) as well as procedural (i.e. organizational routines). Coopetitive tensions and their resolution are related to the use or neglect of both types of practices. Furthermore, interactional and procedural practices are mutually interdependent and can complement each other in tension management in various ways.
Practical implications
The findings of this study shed light on the roles and activities of actual practitioners involved in coopetition, and shows how their work and practices in-use contribute to coopetition, related tensions and their resolution.
Originality/value
By adopting the strategy-as-practice approach, this study generates valuable insights into the practices and tensions in coopetition, as well as illuminates the roles of the practitioners involved in managing coopetition relationships